2007
DOI: 10.1111/j.1365-2990.2006.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 and ‐2 and their relationship to cerebral amyloid angiopathy in Alzheimer's disease

Abstract: Cerebral amyloid angiopathy (CAA) affects over 90% of patients with Alzheimer's disease (AD) and increases the risk of cerebral haemorrhage and infarction. Caveolae--cholesterol-enriched plasmalemmal microinvaginations--are implicated in the production of amyloid beta peptide (Abeta). Caveolin-1 (CAV-1) is essential for the formation of caveolae. Caveolin-2 (CAV-2) is expressed at the plasma membrane only when in a stable hetero-oligomeric complex with CAV-1. CAV-1 and CAV-2 are highly co-expressed by endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The role of caveolin-1 in the CNS [41] in the context of neuronal plasticity [18] and Alzheimer's disease [17,42] is well known, and neurological abnormalities have been reported in caveolin-1 knock-out mice [43]. Additionally, caveolin-1 has a pivotal role in cerebral ischemic injury, blocking production of NO via iNOS [23,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of caveolin-1 in the CNS [41] in the context of neuronal plasticity [18] and Alzheimer's disease [17,42] is well known, and neurological abnormalities have been reported in caveolin-1 knock-out mice [43]. Additionally, caveolin-1 has a pivotal role in cerebral ischemic injury, blocking production of NO via iNOS [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling and plasticity from cerebral ischemia require cholesterol redistribution and synthesis for the formation of new neuronal cell membrane component therefore cholesterol plays a central role in membrane compartmentalization [14,16]. Cholesterol is localized in the caveolae of cellular membranes, and caveolins bind cholesterol and transport it to injured areas [17]. These properties of caveolins suggest that they play a critical role in cell membrane remodeling and synaptic plasticity from cerebral ischemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cav-1 was elevated in Parkin KOMEF cells, a cell model of Parkinson's disease [12]. Upregulation of Cav-1 increased alpha-secretase activity which led to increasing α -secretase-mediated cleavage of amyloid precursor protein; down-regulation of Cav-1 increased accumulation of Aβ in AD [13, 14]. Furthermore, Cav-1 has been shown as a direct target of miR-124 and miR-124-3p [3, 15] .…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding caveolin-2 usually co-expressed with caveolin-1. Caveolin-2 combined with caveolin-1 to form heterogeneous oligomers, and is important for the formation of caveolae (Van Helmond et al 2007). In our study, the immunohistochemistry and western blot analysis revealed that the expression level of caveolae structure proteins caveolin-1 and caveolin-2 in BMECs was increased after VEGF injection, peaked at 45 min, and then decreased to the untreated level.…”
Section: Discussionmentioning
confidence: 98%